UPAYA GERAKAN ME TOO DALAM MENGHADAPI KEKERASAN DAN PELECEHAN SEKSUAL TERHADAP PEREMPUAN DI KOREA SELATAN - triyanti, febi; Yohana S.M Hutabarat , Indri; Sarita, Rahma; Rachmawati , Sekar (Regalia: Jurnal Riset Gender dan Anak, 2023)
The issue of sexual violence against women is an issue that can be found in various countries, both in developed and developing countries. As one of the developed countries, South Korea also has many issues regarding sexual violence against women in its country. This happens as a result of the patriarchal culture and Confucianism inherent in South Korean society itself. This causes the existence of a superior that is owned by men to control and dominate women. This is certainly an impetus for men to commit violence and sexual harassment against women because women are placed as objects of male sexuality. In fact, as fellow human beings, men and women should be able to have the same rights and be at the same level without dominating or making one of them a mere sexual object. Therefore, in response to this, a lot of feminist movements have sprung up in South Korea, one of which is the Me Too movement which seeks to empower women and fight against patriarchal culture to get equal rights with men through campaigns both at home and abroad. social media or directly